O kozah in ljudeh - Durić, Dejan (Slavistična revija, 2018)
Literature is the medium in which memory can be constructed, thematised and transmitted. The subject of analysis in this paper is memory of communism in Macedonian novel Time of Goats by Luan Starova (1993). In the novel emphasis is on a subjective and confessional perspective which is framed by the vow of allegorism. It contemplates the historical context of Tito's disengagement with Stalin and the attempt to create a new working class as the main driver of social and economic development in afterwar Yugoslavia.
Keywords: "Čas koz"; alegorija; Balkan; Balkans; communism; komunizem; Macedonian literature; makedonska književnost; makedonska proza; makedonski pisatelji; Starova, Luan, 1941-